REWARDS, PUNISHMENTS, AND THEIR IMPLICATIONS FOR IMPROVING THE PERFORMANCE OF EDUCATORS IN ISLAMIC BOARDING SCHOOLS - Wan Jamaluddin; Yetri Hasan; Halimatus Sa’diyah (MANAGERE : Indonesian Journal of Educational Management, 2022)
This study aims to analyze rewards, punishments, and their implications for improving the performance of educators at Darul Huffaz Islamic Boarding School Pesawaran - Lampung. This study uses a qualitative case study approach, where the researcher uses interviews, observations, and documentation to obtain valid and accurate data. The study results show that appreciation in an organization is essential because it appreciates those who have tried to change the way they work. Sanctions can weaken behavior and reduce the frequency of subsequent behavior, usually consisting of requesting an unintended consequence. This research uses qualitative descriptive methods in research and interview techniques. Based on the data obtained from the implementation of reward and punishment and its implications for improving the performance of educators at the Darul Huffaz Islamic boarding school Pesawaran - Lampung, it can be concluded that the implementation of reward, and punishment for educators at the Darul Huffaz Islamic boarding school Pesawaran - Lampung is appropriate and the implications can improve performance educators at the Darul Huffaz Islamic boarding school Pesawaran – Lampung.